The Effect of the Zoning System, Student Resilience and Student Self-Efficacy on Learning Achievement in Gresik Regency Public Junior High Schools - Sri Mulyaningsih; Karwanto Karwanto; Muhammad Sholeh (Dinasti International Journal of Education Management And Social Science, 2025)
Education is a fundamental element in the development of adaptive and competitive human resources, especially in the midst of globalization and rapid technological advances. To realize equal access and quality of education, the Indonesian government has implemented a zoning system policy, which aims to reduce the gap between schools. However, the implementation of this policy has raised new challenges, such as inequality in student academic input and a decline in quality in leading schools. On the other hand, student learning achievement is also influenced by internal psychological factors, including resilience in dealing with pressure and self-efficacy, namely students' belief in their academic abilities. This study aims to analyze the effect of the zoning system, student resilience, and self-efficacy on the learning achievement of junior high school students in Gresik Regency. This study uses a quantitative approach with an explanatory survey method. The population in this study were all grade VIII students at Junior High Schools in Gresik Regency, with a sample size of 250 students selected through proportional random sampling techniques. The research instrument was a Likert Scale questionnaire that had been tested for validity and reliability. The data were analyzed using multiple linear regression techniques to determine the partial and simultaneous effects between variables. The results of this study are expected to provide empirical contributions to zoning policies based on student characteristics, as well as support the development of psychopedagogical interventions to improve learning achievement evenly and fairly.